Comparative Evaluation of Three Purification Methods for the Nucleocapsid Protein of Newcastle Disease Virus from Escherichia coli Homogenates. - Yan, Peng Tan; Tan, Chuan Ling; Yusoff, Khatijah; Wen, Siang Tan; Beng, Ti Tey (2005)
In the present study, the performances of conventional purification methods, packed bed adsorption (PBA), and expanded bed adsorption (EBA) for the purification of the nucleocapsid protein (NP) of Newcastle disease virus (NDV) from Escherichia coli homogenates were evaluated. The conventional methods for the recovery of NP proteins involved multiple steps, such as centrifugation, precipitation, dialysis, and sucrose gradient ultracentrifugation. For the PBA, clarified feedstock was used for column loading, while in EBA, unclarified feedstock was used. Streamline chelating immobilized with Ni^2^+ ion was used as an affinity ligand for both PBA and EBA. The final protein yield obtained in conventional and PBA methods was 1.26% and 5.56%, respectively. It was demonstrated that EBA achieved the highest final protein yield of 9.6% with a purification factor of 7. Additionally, the total processing time of the EBA process has been shortened by 8 times compared to that of the conventional method.